2019
DOI: 10.1108/mip-12-2018-0577
|View full text |Cite
|
Sign up to set email alerts
|

Validating action and social alignment constituents of collaboration in business relationships

Abstract: Purpose The purpose of this paper is to test hypothesized relationships within and between the domains of action and social alignment based on a sales perspective in business relationships. Design/methodology/approach This study is based on a cross-industrial sample of Norwegian companies consisting of 213 key informants corresponding to a valid response rate of 40.7 percent. Findings The findings validate that coordination relates positively to economic satisfaction (ES); coordination does not relate to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…In a business-to-business context, satisfaction represents an overall evaluation of, feeling about or attitude to the other party in a relationship or the relationship itself, with the evaluation process encompassing both the economic and the social aspects of the relationship experience (Sanzo et al , 2003). As a result, several authors support the notion that satisfaction in business relationships is not a unidimensional construct but are two distinct constructs, namely, economic satisfaction and non-economic satisfaction (Høgevold et al , 2019; Payan et al , 2019; Mpinganjira et al , 2017; Ferro et al , 2016; Del Bosque et al , 2006; Farrelly and Quester, 2005). As distinct constructs, it can be expected that each will have different antecedents, and thus failure to distinguish between these two satisfaction types will lead to contradictory research results (Geyskens and Steenkamp, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 94%
See 3 more Smart Citations
“…In a business-to-business context, satisfaction represents an overall evaluation of, feeling about or attitude to the other party in a relationship or the relationship itself, with the evaluation process encompassing both the economic and the social aspects of the relationship experience (Sanzo et al , 2003). As a result, several authors support the notion that satisfaction in business relationships is not a unidimensional construct but are two distinct constructs, namely, economic satisfaction and non-economic satisfaction (Høgevold et al , 2019; Payan et al , 2019; Mpinganjira et al , 2017; Ferro et al , 2016; Del Bosque et al , 2006; Farrelly and Quester, 2005). As distinct constructs, it can be expected that each will have different antecedents, and thus failure to distinguish between these two satisfaction types will lead to contradictory research results (Geyskens and Steenkamp, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…Similarly, Geyskens et al (1999) argue that satisfaction as a performance outcome contains both economic and non-economic (social) aspects. Despite previous research establishing that business customers’ satisfaction is not a unidimensional construct, but rather as a composite of both economic and non-economic satisfaction (Høgevold et al , 2019; Payan et al , 2019; Del Bosque et al , 2006; Sanzo et al , 2003; Geyskens and Steenkamp, 2000), no studies could be found that incorporates this multidimensionality together with perceived value in a business-to-business context.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The importance of distinguishing between economic and non-economic satisfaction lies therein that each has a distinct focus (Ulaga & Eggert, 2006), holds varying relationships with various antecedents and outcomes (Geyskens et al, 1999) and failure to differentiate between them will diminish organizations' ability to successfully manage customer relationships (Geyskens & Steenkamp, 2000). Researchers have thus increasingly adopted both economic and non-economic satisfaction as separate constructs when studying business relationships (Glavee-Geo, 2019;Høgevold et al, 2019;Payan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%